Pendistribusian Informasi Pemadaman Listrik PLN Berbasiskan SMS Gateway - Zulafwan Zulafwan; Etika Melsyah Putri (Ikatan Ahli Informatika Indonesia, 2018)
PLN (Perusahaan Listrik Negara), Announcement of electricity blackout schedule published in newspapers, social media or PLN website, the problem is not all people will see the information the. if the blackout due to technical obstacles, then PLN electricity will be extinguished without any previous information. The system is built using SMS Gateway as a media distribution of information about power outages. The system was built using Gammu as its SMS gateway application and PHP with Codeigniter Framework. With this system, information about PLN's power outage will be easily distributed, targeted and acceptable to PLN customers.